A review of iodine-based compounds, with a focus on biofilms: results of an expert panel. (1st July 2020) - Wolcott, Randall D; Cook, Randall G; Johnson, Eric; Jones, Curtis E; Kennedy, John P; Simman, Richard; Woo, Kevin; Weir, Dot; Schultz, Gregory; Hermans, Michel HE
Abstract : Biofilms play a central role in the chronicity of non-healing lesions such as venous leg ulcers and diabetic foot ulcers. Therefore, biofilm management and treatment is now considered an essential part of wound care. Many antimicrobial treatments, whether topical or systemic, have been shown to have limited efficacy in the treatment of biofilm phenotypes. The antimicrobial properties of iodine compounds rely on multiple and diverse interactions to exert their effects on microorganisms. An expert panel, held in Las Vegas during the autumn Symposium on Advanced Wound Care meeting in 2018, discussed these properties, with the focus on iodine and iodophors and their effects on biofilm prevention and treatment.